Technology Acceptance Model (TAM) Approach in the Financial Services Platform for Msme Sector - Y. Johny Natu Prihanto (Conference Series, 2020)
This report aims to explore the determinants of Indonesia's financial service industry. Trust element is the qualitative component of financial technology implementation. According to the Technology Adoption Model ( TAM), action is determined by the decision to use a given device, which in turn is determined by the expected utility and ease of usage of the method. Study models and questionnaires were planned and administered to 175 small and medium business owners in Bogor, West Java, Indonesia. A Structural Equation Model (SEM) study was used. Results found that the dimensions of vector confidence (benevolence, honesty, reputation, problem-solving orientation) have a major impact on the decision to use financial technology explicitly and indirectly by perceived utility, perceived user-friendliness, and financial technology attitude. The managerial consequences of this study are that Indonesia's financial services industry leaders should recognize the impact of technology adoption actions not only by improving perceived user-friendliness and utility, but also by fostering honesty, reputation, benevolence, and problem-solving orientation.